Langerhans Cells From Mice at Birth Express Endocytic- and Pattern Recognition-Receptors, Migrate to Draining Lymph Nodes Ferrying Antigen and Activate Neonatal T Cells in vivo - Becerril-García, Miguel Angel; Yam-Puc, Juan Carlos; Maqueda-Alfaro, Raúl; Beristain-Covarrubias, Nonantzin; Heras-Chavarría, Monica; Gallegos-Hernández, Isis Amara; Calderón-Amador, Juana; Munguía-Fuentes, Rosario; Donis-Maturano, Luis; Flores-Langarica, Adriana; Flores-Romo, Leopoldo (Frontiers in Immunology, 2020)
Antigen capturing at the periphery is one of the earliest, crucial functions of antigen-presenting cells (APCs) to initiate immune responses. Langerhans cells (LCs), the epidermal APCs migrate to draining lymph nodes (DLNs) upon acquiring antigens. An arsenal of endocytic molecules is available to this end, including lectins and pathogen recognition receptors (PRRs). However, cutaneous LCs are poorly defined in the early neonatal period. We assessed endocytic molecules expression in situ: Mannose (CD206)-, Scavenger (SRA/CD204)-, Complement (CD2l, CDllb)-, and Fc-Receptors (CD16/32, CD23) as well as CD1d, CD14, CD205, Langerin (CD207), MHCII and TLR4 in unperturbed epidermal LCs from both adult and early neonatal mice. As most of these markers were negative at birth (day 0), LC presence was revealed with the conspicuous, epidermal LC-restricted ADPase (and confirmed with CD45) staining detecting that they were as numerous as adult ones. Unexpectedly, most LCs at day 0 expressed CD14 and CD204 while very few were MHCII+ and TLR4+. In contrast, adult LCs lacked all these markers except Langerin, CD205, CD11b, MHCII and TLR4. Intriguingly, the CD204+ and CD14+ LCs predominant at day 0, apparently disappeared by day 4. Upon cutaneous FITC application, LCs were reduced in the skin and a CD204+MHCII+FITC+ population with high levels of CD86 subsequently appeared in DLNs, with a concomitant increased percentage of CD3+CD69+ T cells, strongly suggesting that neonatal LCs were able both to ferry the cutaneous antigen into DLNs and to activate neonatal T cells in vivo. Cell cycle analysis indicated that neonatal T cells in DLNs responded with proliferation. Our study reveals that epidermal LCs are present at birth, but their repertoire of endocytic molecules and PRRs differs to that of adult ones. We believe this to be the first description of CDl4, CD204 and TLR4 in neonatal epidermal LCs in situ. Newborns’ LCs express molecules to detect antigens during early postnatal periods, are able to take up local antigens and to ferry them into DLNs conveying the information to responsive neonatal T cells.